Improving Students Critical Thinking through STEAM-PjBL Learning - Ika Priantari; Aulya Nandha Prafitasari; Dwi Retno Kusumawardhani; Siti Susanti (Bioeducation Journal, 2020)
The industrial revolution 4.0 era affected people’s lives, as well as the education system and student learning. The world of education must be able to create and design learning life skills for the 21st century, which one of it is critical thinking skills. Efforts are made by applying the STEAM approach and using the PjBL model. The research was carried out at SMP Muhammadiyah 6 Wuluhan Jember, control class VII B and experiment class VII A. Material KD. 3.8 Analyzing the occurence of environmental pollution and its impact on the ecosystem. The result of the sig (2-tailed) value is 0.046, which indicates that hypotesis is accepted. To be conclude, the STEAM approach and PjBL model have a positive affect on students’ critical thinking skills.